Anggaran Belanja Modal Pemerintah Desa di Kabupaten Poso: Mengalir Kemana? - Syamsul Syamsul (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
This research aims to analyze the allocation of village capital expenditure in Poso Regency. This research uses secondary data obtained from village government general cash book reports from 2019-2022. The data obtained was then analyzed using descriptive analysis techniques. The results of the analysis show that the majority of village government capital expenditure in Poso Regency goes to the construction of roads, irrigation and buildings. On the other hand, a small number of village governments allocate village capital expenditure for land acquisition, vehicle purchases, bridge construction, network construction and other assets. This research is useful in providing information about the main priorities for allocating village capital expenditure.